2017
DOI: 10.1098/rsta.2016.0081
|View full text |Cite
|
Sign up to set email alerts
|

A statistical state dynamics approach to wall turbulence

Abstract: One contribution of 14 to a theme issue 'Toward the development of high-fidelity models of wall turbulence at large Reynolds number' . This paper reviews results obtained using statistical state dynamics (SSD) that demonstrate the benefits of adopting this perspective for understanding turbulence in wall-bounded shear flows. The SSD approach used in this work employs a second-order closure that retains only the interaction between the streamwise mean flow and the streamwise mean perturbation covariance. This c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 83 publications
1
56
0
Order By: Relevance
“…Farrell & Ioannou (2012) used the RNL system with a stochastic forcing (see also the overview in Farrell et al (2017)). Their results confirmed that this RNL system supports a realistic self-sustaining process (SSP).…”
Section: Introductionmentioning
confidence: 99%
“…Farrell & Ioannou (2012) used the RNL system with a stochastic forcing (see also the overview in Farrell et al (2017)). Their results confirmed that this RNL system supports a realistic self-sustaining process (SSP).…”
Section: Introductionmentioning
confidence: 99%
“…The original d nonlinear equations F from (1) are recovered by differentiating (13) with respect to the vector P. Associated with the original system (1) are an infinite hierarchy of cumulant equations,…”
Section: The Cumulant Generating Functionalmentioning
confidence: 99%
“…Fortunately, heterogeneous flows that are dominated by the interaction of eddies with a mean shear are amenable to relatively simple closures, because the evolution of third-order cumulants, describing eddy-eddy interactions, can sometimes be neglected [16]. Statistical state dynamics, or direct statistical simulation [46,1] has therefore been applied with success in simulations of planetary jets [37,47,14,7] and wall-bounded shear-flow [17,13]. Whilst strongly nonlinear systems, such as the model for Rayleigh-Bénard convection given by the Lorenz equations [31], require a more sophisticated treatment that accounts for the role of cumulants beyond second order, direct statistical simulation can nevertheless produce accurate predictions [2].…”
Section: Introductionmentioning
confidence: 99%
“…An emerging theme underlying a number of recent model constructions (such as RNL [42] and the resolvent model framework [11]) is that linear mechanisms play a greater role in the overall dynamics than perhaps previously imagined, and especially so with increasing Reynolds number. The contribution by Cossu & Hwang [12] summarizes their recent results, revealing elements that simultaneously incorporate a number of the physical and conceptual features studied by other authors in this theme issue.…”
Section: (C) Model Reductions That Selectively Restrict Nonlinear Intmentioning
confidence: 99%
“…[41]). In their contribution, Farrell et al [42] describe how the RNL ideas can be employed within a statistical state dynamics (SSD) framework that respectively represents the mean velocity and Reynolds stresses by the first and second cumulant of ensemble averages. These ensemble averages are constructed using a Leray projection of the Navier-Stokes equations and by employing temporal white noise forcing to generate the members of the ensemble.…”
Section: (C) Model Reductions That Selectively Restrict Nonlinear Intmentioning
confidence: 99%